1978
DOI: 10.1111/j.1432-1033.1978.tb12233.x
|View full text |Cite
|
Sign up to set email alerts
|

ABH‐Blood‐Group Antigens and Glycolipids of Human Saliva

Abstract: The nature of ABH-blood-group antigens in saliva was investigated. Human saliva was examined serologically for ABH-blood-group activity in its native form and after various treatments. The activity of the native form persisted in the delipidated samples, but was entirely lost after alkaline degradation. The lipid portion of saliva was completely inactive in the ABH hemagglutination inhibition system. The same results were obtained when purified glycolipid fraction of saliva was used instead of whole lipid extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…In addition to expression on red blood cells, ABO(H) glycan structures are expressed in extracellular fluids, such as saliva, tears, and breast milk, and at the surface of oral epithelial cells (13). The human blood group antigen classification system is based on three glycan structures, A, B and H, with precursors lacto- N -tetraose (LNT; Gal-β-1,3-GlcNAc-β-1,3-Gal-β-1,4-Glc), lactosamine type 1 (Galβ1-3GlcNAc), and lactosamine type 2 (Galβ1-4GlcNAc) forming the major backbone of all three antigens (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to expression on red blood cells, ABO(H) glycan structures are expressed in extracellular fluids, such as saliva, tears, and breast milk, and at the surface of oral epithelial cells (13). The human blood group antigen classification system is based on three glycan structures, A, B and H, with precursors lacto- N -tetraose (LNT; Gal-β-1,3-GlcNAc-β-1,3-Gal-β-1,4-Glc), lactosamine type 1 (Galβ1-3GlcNAc), and lactosamine type 2 (Galβ1-4GlcNAc) forming the major backbone of all three antigens (4).…”
Section: Introductionmentioning
confidence: 99%
“…Host gene expression of α-1,2-fucosyltransferase enables synthesis of H antigen, which can be further transformed by N -acetylgalactosaminyl-transferase or d -galactosyl-transferase to produce A and B antigens, respectively (5, 6). Expression of A, B, and H antigens on epithelial cell surfaces and secretion into extracellular fluid is dependent on expression of the Se( FUT2 ) gene encoding fucosyl-transferase 2, which facilitates secretion of the corresponding blood group antigens by mucin-secreting goblet cells (1). Population studies have shown that on average, 76% of people are blood group antigen secretors and 24% are nonsecretors (7).…”
Section: Introductionmentioning
confidence: 99%
“…4 The secretor gene encodes for enzymes (glycosyltransferases), which become active in mucin-secreting cells like goblet and mucous cells of mucous membranes and different glands, resulting in the secretion of the corresponding blood group antigens in the body fluids. 5 H antigen that is present on the cells of individuals with O blood group is the base for A and B antigens, but A and B antigens differ only in their added terminal sugars, which are controlled by specific enzymes called transferase enzymes. These enzymes are under the control of inherited genes, which are A, B, H (FUT1) genes and secretor (FUT2) genes.…”
Section: Introductionmentioning
confidence: 99%
“…FUT2 encodes the enzyme galactoside 2-alpha-L-fucosyltransferase 2 (FUT2), a Golgi stack membrane protein that contributes to the synthesis of an H antigen precursor and of relevance to the Lewis blood group system. Subjects with at least one functional FUT2 allele are referred to phenotypically as secretors, characterized by the additional presence of ABH antigens in plasma other bodily fluids(Slomiany and Slomiany 1978). Our findings for both CHN and our meta-analysis demonstrate independent associations of population-specific functional FUT2 knockout variants, lending credence to the non-secretor phenotype playing a large role in E-cadherin circulation.…”
Section: Discussionmentioning
confidence: 99%